Pengaruh Kualitas Layanan dan Harga terhadap Kepuasan Pelanggan dengan Keputusan Pembelian sebagai Variabel Mediasi pada Jasa Transportasi Bus PT Anas Nasional Sejahtera (ANS) Rute Padang-Jakarta - Vidasanty, Sekar; Rino, Rino (Jurnal Salingka Nagari, 2024)
The purpose of this research was to determine the impact of Service Quality and Price on Customer Satisfaction on PT ANS Bus transportation services on the Padang-Jakarta route. The population in this research are consumers who use the ANS bus and the determination of the number of samples using the Purposive Sampling technique with the consideration that consumers make Purchase Decisions for ANS Bus services on the Padang-Jakarta route. The data used is the type of primary data that is processed through the distribution of questionnaires to consumers who use the Padang-Jakarta ANS Bus route. The results is (1) Service Quality had no significant effect on Customer Satisfaction, (2) Price had a significant effect on Customer Satisfaction, (3) Price had a significant effect on Service Quality, (4) Service Quality had a significant effect on which has a significant effect on Purchase Decisions, (5) Price has a significant effect on Purchase Decisions, (6) Purchase Decisions has a significant influence on Customer Satisfaction, (7) Service Quality has a significant influence on Customer Satisfaction with Purchase Decisions as a mediating variable, (8) Price has a significant effect on Customer Satisfaction with Purchase Decisions as a mediating variable.